2014
DOI: 10.4103/1947-2714.141636
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of loss to follow-up in patients living with HIV/AIDS after initiation of antiretroviral therapy

Abstract: Background:Long-term regular follow up of ART is an important component of HIV care. Patients who are lost to follow-up (LTFU) while on treatment compromise their own health and the long-term success of ART programs.Aim:This study was aimed at determining the incidence and risk factors for LTFU in HIV patients on ART at ART clinic of Mizan-Aman General Hospital, Ethiopia.Materials and Methods:A retrospective cohort study of 2133 people living with HIV/AIDS and attending an ART clinic between 2005 and 2013 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
68
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(86 citation statements)
references
References 32 publications
14
68
1
Order By: Relevance
“…Without the availability of, and access to, these basic tests, monitoring for ART toxicity cannot be performed, and could compromise the long-term effectiveness and sustainability of the ART program. Researches have showed that HIV patients on ART who have regimen substitution due to drug toxicity/drug related adverse reactions were at higher risk of loss to follow-up [44, 45] which may partly explain the significant reduction in number of patients in care after five years of follow-up reported from study included in this review [19]. …”
Section: Discussionmentioning
confidence: 99%
“…Without the availability of, and access to, these basic tests, monitoring for ART toxicity cannot be performed, and could compromise the long-term effectiveness and sustainability of the ART program. Researches have showed that HIV patients on ART who have regimen substitution due to drug toxicity/drug related adverse reactions were at higher risk of loss to follow-up [44, 45] which may partly explain the significant reduction in number of patients in care after five years of follow-up reported from study included in this review [19]. …”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in Aksum St Marry Hospital[8], Mizan Aman General Hospital[10], Jimma University Specialized Hospital[23] and University of Gondar[24] reported that the proportion of LTFU was 9.8%, 26.7%, 28% and 31.4%, respectively. Additionally, a retrospective study from Ethiopia reported that retention of patients in care was a major challenge and varied across health facilities[25].…”
Section: Introductionmentioning
confidence: 99%
“…Primary studies conducted in Ethiopia reported socio-demographic, behavioral, clinical and institutional factors as contributors to discontinuation[7–10]. However, different studies showed conflicting association, and the existence of additional factors challenging interventions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the existing literature, there are reports that have evaluated the association between CD4 + at cART initiation and loss to follow-up (LTFU). However, these results are conflicting [2528] and are less relevant, as treatment guidelines have evolved substantially regarding cART initiation eligibility [17,29]. Some studies, although few, have looked at other mechanisms that may be related to mortality outcomes by CD4 + at cART initiation [30–36].…”
Section: Introductionmentioning
confidence: 99%